Atypical anatomy of premolars in Saudi population, It’s prevalence and treatment: A case report series - Nawaf Almutairi; Ibrahim Alhariqi; Saleh Alshudukhi; Yahya Alharbi; Badar Alharbi; Hanin Alsalhi; Badi Alotaibi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The anatomical variations of canal configuration is a challenging clinical situation, both at the diagnostic and treatment levels. The present case series aims to describe the management of mandibular and maxillary premolars with extra roots and different anatomy configurations. Five Saudi patients were referred to the Endodontic department for the management of mandibular and maxillary premolars that appeared unusual radiographically. To negotiate, clean, and shape the root canal system, modern endodontic tools such as a dental operating microscope and nickel-titanium files were used. A follow-up period ranging from 6 months to 1 year revealed ongoing periapical healing of premolars with lesions, while the premolars without periapical lesions were free of any signs and symptoms with normal apical tissues.